Vertical Distribution of Photosynthetic Nitrogen Use Efficiency and Its Response to Nitrogen in Field‐Grown Maize. Issue 1 (1st January 2016) - Chen, Yanling; Wu, Dali; Mu, Xiaohuan; Xiao, Changxin; Chen, Fanjun; Yuan, Lixing; Mi, Guohua
ABSTRACT: During the grain‐filling period in maize ( Zea mays L.), increasing photosynthesis per unit plant N, namely photosynthetic N‐use efficiency (PNUE) is a potential way to increase N‐utilization efficiency (NUtE). This study aimed to understand whether the spatial distribution of PNUE within the canopy is optimized under low N conditions as a method of maximizing canopy productivity. Maize plants were grown in the field for 2 yr with three N levels (0, 180, 240 kg N ha −1 ). Changes in specific leaf N (SLN), net photosynthetic rate ( P N ), PNUE (calculated as P N /SLN), stomatal conductance ( g s ), green leaf area (GLA), and light interception of leaves at different positions were measured every 10 d after silking (DAS). Significant differences in SLN, P N, g s, and PNUE occurred among leaves at different positions: upper leaf ≥ ear leaf > lower leaf. A positive correlation was found between the spatial difference in g s and that in PNUE and in P N . Compared with the average of N180 and N240 across 2 yr, grain yield (GY) decreased by 56% but physiological NUtE increased by 22% without N (N0). Correspondingly, PNUE increased by 44, 25, and 35% in the lower, ear, and upper leaves, respectively. Light interception by the middle leaves was unchanged with N0. We concluded that the vertical distribution of PNUE was optimized with the light distribution pattern in the canopy. The greater whole‐plant NUtE we found with N0 may be explained by the overall increase in PNUE in the leaves and the continued interception of light by middle leaves.